1997
DOI: 10.1046/j.1365-2362.1997.1060658.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fasting insulin and cardiovascular risk factors is already present in young men: the Verona Young Men Atherosclerosis Risk Factors Study

Abstract: The associations between fasting plasma insulin concentration and risk factors for cardiovascular diseases were examined in 979 18-year-old men participating in the Verona Young Men Atherosclerosis Risk Factors Study, a cross-sectional population-based study. Body mass index (BMI), waist-to-hip ratio (WHR), plasma triglycerides and uric acid concentrations, and blood pressure values significantly increased, and the high-density lipoprotein (HDL)-total cholesterol ratio decreased, across quartiles of fasting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(103 reference statements)
2
7
0
Order By: Relevance
“…With the exception of triglycerides and HDL in 18-19-year-old male adolescents, associations among insulin, lipids, and lipoproteins disappeared. These results are similar to those reported by Bonora et al, 15 except that those authors found no association with HDL. Other studies have found that insulin resistance is also related with LDL and VLDL, 16,17 but these associations may have been confounded because BMI, WC, and EE were not controlled.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With the exception of triglycerides and HDL in 18-19-year-old male adolescents, associations among insulin, lipids, and lipoproteins disappeared. These results are similar to those reported by Bonora et al, 15 except that those authors found no association with HDL. Other studies have found that insulin resistance is also related with LDL and VLDL, 16,17 but these associations may have been confounded because BMI, WC, and EE were not controlled.…”
Section: Discussionsupporting
confidence: 92%
“…There is controversy concerning this matter, as some researchers have found that triglycerides are positively associated with insulin, whereas others have also found associations with LDL, HDL, and VLDL. [15][16][17] Total cholesterol has not been associated with insulin. [15][16][17] Furthermore, the association between insulin, abdominal fat, blood lipids, and lipoproteins in adolescents is not as clear as it is in adults.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The higher caloric intake among LC participants may ameliorate the metabolic response to caloric restriction seen in very-low-energy diets. Increased serum insulin is known to promote lipogenesis, and some of the known sequelae of low insulin states, such as lowered TG, 42 were observed in the LC group. Perhaps insulin production or insulin activity is affected by LC dieting.…”
Section: Discussionmentioning
confidence: 94%
“…Epidemiological studies have shown an association between hyperinsulinemia and coronary atherosclerosis (36,37), as well as clustering of cardiovascular disease risk factors (38)(39)(40). To test for an association between insulin levels and atherosclerosis susceptibility in our mouse model, we compared mean fasting insulin levels in a subset of Mbc-Ldlr0 mice grouped by genotype at the Chr 4 and Chr 6 QTLs.…”
Section: Resultsmentioning
confidence: 99%